National Health Interview Survey, 2005 ([Verlag nicht ermittelbar], 2006)
The purpose of the National Health Interview Survey (NHIS) is to obtain information about the amount and distribution of illness, its effects in terms of disability and chronic impairments, and the kinds of health services people receive. Implementation of a redesigned NHIS, consisting of a basic module, a periodic module, and a topical module, began in 1997 (see NATIONAL HEALTH INTERVIEW SURVEY, 1997 [ICPSR 2954]). The 2005 NHIS contains the Household, Family, Person, Sample Adult and Sample Child files from the basic module. Each record in the Household-level File (Part 1) contains data on type of living quarters, number of families in the household responding and not responding, and the month and year of the interview for each sampling unit. The Family-level File (Part 2) is made up of reconstructed variables from the person-level data of the basic module and includes information on sex, age, race, marital status, Hispanic origin, education, veteran status, family income, family size, major activities, health status, activity limits, and employment status, along with industry and occupation. As part of the basic module, the Person-level File (Part 3) provides information on all family members with respect to health status, limitation of daily activities, cognitive impairment, and health conditions. Also included are data on years at current residence, region variables, height, weight, bed days, doctor visits, hospital stays, and health care access and utilization. A randomly-selected adult in each family was interviewed for the Sample Adult File (Part 4) regarding respiratory conditions, use of nasal spray, renal conditions, AIDS, joint symptoms, health status, limitation of daily activities, and behaviors such as smoking, alcohol consumption, and physical activity. The Sample Child File (Part 5) provides information from an adult in the household on medical conditions of one child in the household, such as respiratory problems, seizures, allergies, and use of special equipment like hearing aids, braces, or wheelchairs. Also included are variables regarding child behavior, the use of mental health services, and Attention Deficit Hyperactivity Disorder (ADHD) as well as responses to the SDQ-EX, which is the extended version of the Strengths and Difficulties questionnaire on child mental health. The 2005 data contain the Child Mental Health Brief (CMB), Child Mental Health Services (CMS) and Child Influenza Immunization (CFI) sections. The Injury/Poison Episode File (Part 6) is an episode-based file that contains information about the external cause and nature of the injury or poisoning episode and what the person was doing at the time of the injury or poisoning episode, in addition to the date and place of occurrence. The Injury/Poison Episode Verbatim File (Part 7) contains edited narrative text descriptions of the injury or poisoning, provided by the respondent. The Sample Adult Cancer File (Part 8) has been added in 2005 and examines diet and nutrition, physical activity, tobacco use, cancer screening, genetic testing, and family history. Imputed income files for 2005 are now available through the NCHS Web site at www.cdc.gov/nhis.